GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 301831 species occurrences available in GBIF matching the query: TaxonKey: Beta Linnaeus, 1753 or Vaccinium L. or Helianthus annuus L. or Corylus L. or Mentha piperita L. (pro. sp.) or Picea omorika (Pancic) Purk. or Taxus Linnaeus, 1753 or Fragaria L. or Pseudotsuga menziesii (Mirb.) Franco or Tsuga Carrière or Thuja L. or Euonymus L. or Rubus idaeus L. Country: United Kingdom or New Zealand or United States or Canada. The dataset includes 301831 records from 239 constituent datasets: 73 records from Bioimages. 2306 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 486 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 11 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 5357 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 92899 records from Botanical Society of the British Isles - Vascular Plants Database. 1 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 2964 records from Consortium of California Herbaria. 680 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 1 records from EPA River Biologists data. 11 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 12 records from SANT herbarium vascular plants collection. 3 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from NCSM PaleoBotany Collection. 6982 records from Consortium of California Herbaria. 320 records from Phanerogamic Botanical Collections (S). 23 records from IAC - Herbário do Instituto Agronômico de Campinas. 2068 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 1223 records from Naturalis Biodiversity Center (NL) - Botany. 3 records from SPF - Herbário da Universidade de São Paulo. 635 records from Harriet Irving Botanical Gardens (HIBG). 6 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 1 records from HUFU - Herbarium Uberlandense. 10 records from Online Atlas of vascular plants 2012-2020. 125 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 3 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 6 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 1 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 3245 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 7 records from NPL collections. 44 records from Species data extracted from the National Vegetation Database. 11 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 903 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 5 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 1372 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 7 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 13 records from OHN. 16 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 1823 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 2 records from Natural History Museum Maastricht (NL) - Herbarium. 2435 records from iNaturalist research-grade observations. 3635 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 2269 records from CONN. 1332 records from UCJEPS TAPIR Provider. 1 records from Herbaria of the University and ETH Zürich. 627 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 1 records from ICN - Herbário do Instituto de Ciências Naturais. 716 records from University of Alberta Vascular Plant Herbarium (ALTA). 10 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 2 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 181 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 4 records from Tallinn Botanic Garden. 757 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 86 records from Australia's Virtual Herbarium. 4 records from HUCS - Herbário da Universidade de Caxias do Sul. 621 records from Louisiana State University Herbarium - Vascular Plants. 1 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 10 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 4 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 67 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 3 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 192 records from Scottish Borders Biological Records Centre - SWT Scottish Borders Local Wildlife Site Survey data 1996-2000 - species information. 496 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 31 records from Ireland's BioBlitz 2012. 27 records from Scottish Natural Heritage - Standing Waters Database. 15 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 374 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 3 records from Irish Vascular Plant Data - Paul Green. 854 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 3 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 72 records from MBM - Herbário do Museu Botânico Municipal. 206 records from Kathryn Kalmbach Herbarium. 67 records from UCBG TAPIR Provider. 242 records from H.A. Stephens Herbarium. 26 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 4 records from Estonian Museum of Natural History. 83 records from Royal Horticultural Society - RHS monitoring of native and naturalised plants and animals at its gardens and surrounding areas. 1 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 33 records from Jardin botanique de Montréal (JBM). 16 records from Nationaal Herbarium Nederland. 2821 records from BSBI tetrad data for Ireland. 1 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 92 records from Ireland's BioBlitz. 18 records from Australian National Herbarium (CANB). 15 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 80 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 2 records from Jardín Botánico de Córdoba: Herbarium COA. 12 records from Herbario de la Universidad de Sevilla, SEV-Historico. 19 records from DAO Herbarium Type Specimens. 56020 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 1 records from Polish gene bank – passport data of plants accessions which are important in human life. 1221 records from R. L. McGregor Herbarium Vascular Plants Collection. 731 records from Botany Division, Yale Peabody Museum. 63 records from Paleobotany Division, Yale Peabody Museum. 9 records from Herbarium Senckenbergianum (FR). 9 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 384 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 9 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (verified). 37 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 250 records from University of Lethbridge Herbarium (LEA). 547 records from University of California Museum of Paleontology. 1 records from ALCB - Herbário Alexandre Leal Costa. 2220 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 1460 records from NMNH occurrence DwC-A. 2277 records from Herbarium of The New York Botanical Garden. 26 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 12 records from The Fungal Collection at the Botanische Staatssammlung München. 23 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 10 records from Base de datos para la xiloteca del Instituto de Biología de la UNAM. 597 records from Canadian Museum of Nature Herbarium. 366 records from Herbarium (UNA). 4 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 302 records from Joint Nature Conservation Committee - Vegetation surveys of coastal shingle in Great Britain. 4031 records from Staffordshire Ecological Record - SER Site-based Surveys. 1 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 274 records from Colorado State University Herbarium. 507 records from MISS_DC_01MAR2006. 44 records from NCSU_Darwincore. 9 records from Lund Botanical Museum (LD). 51 records from National Trust - Ickworth species data held by The National Trust.. 1 records from Pond Conservation - National Pond Monitoring Network collated pond survey data for Great Britain 1972 to 2007. 327 records from Staffordshire Ecological Record - SER Species-based Surveys. 1 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 235 records from Tullie House Museum - Tullie House Museum. Cumbria Wildlife Trust survey records from 1970 - 2007 of Cumbria Wildlife Sites. Various.. 83 records from Botany (UPS). 8 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 12 records from R - Herbário do Museu Nacional. 238 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 16 records from Hertfordshire Biological Records Centre - Hertfordshire Urban Surveys (incomplete). 4 records from Tromsø Museum, Vascular plants. 7 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 3150 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 661 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 46 records from naturgucker. 53 records from National Trust - Hatfield Forest species data held by The National Trust.. 6 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 1 records from MfN - Fossil plants (Cenophytic). 10 records from New Zealand National Vegetation Survey Databank. 6 records from Hertfordshire Biological Records Centre - Hertfordshire Lowland Meadow Inventory Survey 2010. 2596 records from Missouri Botanical Garden. 9 records from Botanical Research Intitute of Texas. 19 records from Natural History Museum, Vienna - Herbarium W. 16 records from Lothian Wildlife Information Centre - Lothian Wildlife Information Centre Secret Garden Survey. 10 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 243 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 5 records from Institut Botanic de Barcelona, BC. 44 records from Botanic Garden of the Finnish Museum of Natural History. 173 records from Royal Botanical Gardens Herbarium. 18 records from herbario. 1782 records from Vascular Plant Collection. 261 records from Arizona State University Vascular Plant Herbarium. 531 records from California State University, Chico. 13 records from NSW herbarium collection. 46 records from Herbarium Berolinense. 5246 records from United States National Plant Germplasm System Collection. 6 records from The Erysiphales Collection at the Botanische Staatssammlung München. 3 records from Nordic Genetic Resources. 293 records from USU-UTC Specimen Database. 16 records from Central Scotland Forest Trust - South Lanarkshire peatland records 2013. 171 records from EKY_Darwincore. 1 records from Lichen Collection - University of Washington Herbarium (WTU). 28 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 5 records from National Trust - Sutton Hoo species data held by The National Trust.. 6 records from Colección de Herbario. 4 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 12 records from Wildlife Sightings. 1 records from Carnet en Ligne. 6 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 148 records from Natural History Museum (London) Collection Specimens. 2028 records from NatureServe Network Species Occurrence Data. 3 records from KNWR Herbarium Collection. 2209 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 1 records from CABI Bioscience Fungus Collection. 2 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 20 records from Herbario de la Universidad de Sevilla, SEV. 74 records from Paleobiology Database. 232 records from Database Schema for UC Davis [Herbarium Labels]. 2 records from The Erysiphales Collection at the University Halle-Wittenberg. 1 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 3342 records from Harvard University Herbaria. 274 records from E.C. Smith Herbarium. 503 records from Specimen Database of Colorado Vascular Plants. 1319 records from EURISCO, The European Genetic Resources Search Catalogue. 38 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 412 records from Field Museum of Natural History (Botany) Seed Plant Collection. 784 records from New Mexico Biodiversity Collections Consortium database. 293 records from UA Herbarium. 5 records from University of Ghana - Ghana Herbarium. 2 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 9 records from UPCB - Herbário do Departamento de Botânica. 2 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 193 records from Geographically tagged INSDC sequences. 12 records from Irish vascular plant data 1999-2009. 1 records from FURB - Herbário Dr. Roberto Miguel Klein. 538 records from Royal Botanic Garden Edinburgh Herbarium (E). 987 records from Michigan State University Herbarium Vascular Plants. 38 records from Flora of County Cavan. 51 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 21 records from Vascular Plant Herbarium, Trondheim (TRH). 19 records from New Zealand Biodiversity Recording Network. 1 records from Wilson Botanical Garden - Las Cruces Biological Station. 2367 records from Green Plant Herbarium (TRT). 4 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007. 1126 records from Bernice P. Bishop Museum. 226 records from University of British Columbia Botanical Garden Collections (UBCBG). 4839 records from Wiltshire and Swindon Biological Records Centre - Wiltshire & Swindon Site-based Survey Records. 2554 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 731 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Survey of Ancient Woodlands in Berkshire.. 1 records from The Bergius Herbarium. 701 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Oxfordshire. 878 records from E. C. Smith Herbarium (ACAD). 3 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 1 records from Geneva Herbarium – General Collection (G). 14409 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 1 records from UESC - Herbário Universidade Estadual de Santa Cruz. 383 records from Botanical Society of the British Isles - SNH Site Condition Monitoring - Vascular plants (2000-2006). 4588 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 54 records from All observations extracted from the Flora of Northumberland and Durham 1831. 90 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 40 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 165 records from Vascular Plant Herbarium, Oslo (O). 8 records from Herbier Boreal Confluence (BOUM). 20 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 126 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 5 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 944 records from Greater Manchester Ecology Unit - Higher Plant Records From Greater Manchester. 1958 records from CAS Botany (BOT). 4474 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 183 records from Allan Herbarium (CHR). 6508 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 128 records from CZE National PGR Inventory. 1 records from Anymals+plants - Citizen Science Data. 6608 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 15 records from Fundación Miguel Lillo - Colección Fanerogámica. 401 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 5 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 2 records from BoGART. 2647 records from Northern Ireland Environment Agency - EHS Species Datasets. 919 records from Botanical Society of the British Isles - Changing Flora of Glasgow 1982-2000.
Keywords: GBIF; biodiversity; species occurrences